Single Supervisory Mechanism as a response to the banking crisis. Analysis with the particular emphasis on the non-euro area EU member state - Pawel Pisany (Institute of Economic Research (IER), 2016)
The aim of this article is to present Single Supervisory Mechanism in the context of challenges in the post-crisis economy. One analyzed the topic from the perspective of non-euro area EU member state. The article consists of three main parts. Firstly, the short literature review related to banking crisis as a background for institutional reforms, was conducted. The second part refers to the legal base of SSM and its impact on the final shape of this institution. In the last part, the negative recommendation in terms of accession of Poland to SSM through OPT-IN procedure, was presented and justified by a simple economic game.
Keywords: E61; G28; G21; 330; Single Supervisory Mechanism; banking regulations; banking crisis